Pengaruh Parameter Proses Pencetakan 3D Printing Terhadap Kebulatan Produk Menggunakan Filament PETG - Wahyudi, Wahyudi; S Suzen, Zaldy; Pristiansyah, Pristiansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
3D printing technology, specifically Fused Filament Fabrication (FFF) or Fused Deposition Modeling (FDM), is a popular manufacturing method that uses thermoplastic to print products layer by layer. However, dimensional accuracy is still a challenge. This study evaluates the effect of 3D printing process parameters on the roundness of PETG-based products, using the Taguchi L9 method. Roundness measurement was performed with an indicator dial. The results showed that the optimal parameters were layer height 0,1 mm,Nozzle temperature 250° ,and print speed 25 mm/s, with an average roundness value of 0,078 and the highest S/N value of 19,934. The most influential factor was layer height, followed by infill density and printing speed. The Taguchi method is effective in optimizing process parameters to improve dimensional accuracy and reduce the number of experiments without compromising data quality